New collected poems - Berry, Wendell, 1934- (Counterpoint : Distributed by Publishers Group West, 2012)
In New Collected Poems, Berry reprints the nearly two hundred pieces in Collected Poems, along with the poems from his most recent collections--Entries, Given, and Leavings--to create an expanded collection, showcasing the work of a man heralded by The Baltimore Sun as "a sophisticated, philosophical poet in the line descending from Emerson and Thoreau . . . a major poet of our time."--publisher description.